2015
DOI: 10.1016/j.actbio.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potential of doxorubicin loaded microbubbles as a theranostic modality using a murine tumor model

Abstract: In this study, a novel phospholipid-based microbubble formulation containing doxorubicin and perfluoropropane gas (DLMB) was developed. The DLMBs were prepared by mechanical agitation of a phospholipid dispersion in the presence of perfluoropropane (PFP)gas. An anionic phospholipid, distearoylphosphatidylglycerol (DSPG) was selected to load doxorubicin in the microbubbles by means of electrostatic interaction. The particle size, zeta potential, echogenicity and stability of the DLMBs were measured. Drug loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 28 publications
(30 reference statements)
0
28
2
Order By: Relevance
“…Blood was taken from the inferior vena cava, and the heart, liver, spleen, lung and kidney were harvested and weighed. Dox and Cur were extracted as reported in a previous study (Abdalkader et al, 2015). Briefly, organs were homogenised using a mixed solution of isopropanol and 1 M HCl (1:1, v/v) and incubated at 4°C for 1 h. The solutions were centrifuged at 1,630 × g for 15 min, and the supernatants were centrifuged again at 15,000 × g for 15 min.…”
Section: Bio-distribution Of the Nanoparticlesmentioning
confidence: 99%
“…Blood was taken from the inferior vena cava, and the heart, liver, spleen, lung and kidney were harvested and weighed. Dox and Cur were extracted as reported in a previous study (Abdalkader et al, 2015). Briefly, organs were homogenised using a mixed solution of isopropanol and 1 M HCl (1:1, v/v) and incubated at 4°C for 1 h. The solutions were centrifuged at 1,630 × g for 15 min, and the supernatants were centrifuged again at 15,000 × g for 15 min.…”
Section: Bio-distribution Of the Nanoparticlesmentioning
confidence: 99%
“…Although the impact of chitosan in the resultant surface tension and Laplace pressure towards the decafluorobutane core as well as shell elasticity behavior in gaseous environments still need to be elucidated, this new composite interface was effective in reducing the C 4 F 10 dissolution dynamics compared to a commonly employed phospholipid shell. Similar composite monolayers of phospholipid mixture intercalated with doxorubicin were also effective in reducing perfluoropropane (C 3 F 8 ) lost along the time, with dependency on drug rate incorporation into the shell (Abdalkader et al, 2015).…”
Section: In Vitro Stability Of Microvesiclesmentioning
confidence: 97%
“…Lipid-coated microvesicles containing a perfluorocarbon gas core are widely employed as ultrasound contrast agents (UCA) in clinical imaging and targeted-release systems of therapeutic agents (Abdalkader et al, 2015;Ferrara, Borden, & Zhang, 2009). Although UCA utilization is recommended in several cardiology assays, the current gas-filled microvesicles generation exhibits low gas permeation resistance and short circulation lifetime (Garg, Thomas, & Borden, 2013;Wilson & Burns, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that MBs loaded with doxorubicin can only be stably prepared with the mechanical agitation method (Abdalkader et al, 2015). During the mechanical agitation method, no significant temperature elevation is generated, which is useful for thermosensitive materials.…”
Section: Introductionmentioning
confidence: 99%